PHILOSOPHICAL ASPECTS OF ABU NASR FOROBI’S VIEWS ON IDEAL SOCIETY: https://doi.org/10.5281/zenodo.14771025 - Spanov, Meirhan; Khosilmurodov, Islam (Journal of Contemporary World Studies, 2025)
This article will be devoted to the philosophical analysis of ethics, one of the forms of being, the views of Abu Nasr Forobi on the ideal society. As a city of positive people, it reveals people’s thoughts about their tasks and management systems in society.